Alchemilla mazandarana (Rosaceae), a new species from high mountainous areas of the Hyrcanian relict region, N. Iran - Naqinezhad, Alireza; Fröhner, Sigurd E.; Esmailpoor, Ali (Phytotaxa, 2017)
Alchemilla mazandarana (Rosaceae) is described and illustrated as a new endemic species from the high mountain rocks of the Hyrcanian region, N. Iran. The new species is characterized by unique leaf division and flower characteristics and most closely related to A. rizensis, A. heteroschista and A. sericea. Some notes are presented on the ecology, distribution, and conservation status of the new species and a distribution map is provided.